Novel aromatic ring-hydroxylating dioxygenase genes from coastal marine sediments of Patagonia - Lozada, Mariana (2008)
Polycyclic aromatic hydrocarbons (PAHs), widespread pollutants in the marine environment, can produce adverse effects in marine organisms and can be transferred to humans through seafood. Our knowledge of PAH-degrading bacterial populations in the marine environment is still very limited, and mainly originates from studies of cultured bacteria. In this work, genes coding catabolic enzymes from PAH-biodegradation pathways were characterized in coastal sediments of Patagonia with different levels of PAH contamination.Genes encoding for the catalytic alpha subunit of aromatic ring-hydroxylating dioxygenases (ARHDs) were amplified from intertidal sediment samples using two different primer sets. Products were cloned and screened by restriction fragment length polymorphism analysis. Clones representing each restriction pattern were selected in each library for sequencing. A total of 500 clones were screened in 9 gene libraries, and 193 clones were sequenced. Libraries contained one to five different ARHD gene types, and this number was correlated with the number of PAHs found in the samples above the quantification limit (r = 0.834, p < 0.05). Overall, eight different ARHD gene types were detected in the sediments. In five of them, their deduced amino acid sequences formed deeply rooted branches with previously described ARHD peptide sequences, exhibiting less than 70% identity to them. They contain consensus sequences of the Rieske type [2Fe-2S] cluster binding site, suggesting that these gene fragments encode for ARHDs. On the other hand, three gene types were closely related to previously described ARHDs: archetypical nahAc-like genes, phnAc-like genes as identified in Alcaligenes faecalis AFK2, and phnA1-like genes from marine PAH-degraders from the genus Cycloclasticus.Conclusion: These results show the presence of hitherto unidentified ARHD genes in this sub-Antarctic marine environment exposed to anthropogenic contamination. This information can be used to study the geographical distribution and ecological significance of bacterial populations carrying these genes, and to design molecular assays to monitor the progress and effectiveness of remediation technologies.